Economic analysis of rubber production affecting the SMR profit price in rubber mill; a case study in FRISB Kilang Getah Pasir Besar, Gemas / Erwin Hazziq Abdul Hamid - Abdul Hamid, Erwin Hazziq (Faculty of Plantation and Agrotechnology, 2018)
The global demand for natural rubber for producing the SMR (Standard Malaysian Rubber) will give a huge impact to the economic and income in our country. In Malaysia, this Standard Malaysian Rubber (SMR) has become a commodity in the international market. According to Malaysian Rubber Board (MRB, 2011), there have many challenge that can affect the internal and external factor on comparative in the SMR production in Malaysia. This study aims to investigate the economic analysis on rubber production factor that affecting the SMR profit price in rubber mill and was conducted in FRISB Kilang Getah Pasir Besar, Gemas. The data for this study was collected by using interview (face to face session) and secondary data collection method. Starting from year 2015 until 2017, the data was collected in the form of monthly data. As the result was analyzed by using Statistical Package for Social Science (SPSS), it showed that there is a significant different relationship between the rubber productions that affecting the SMR profit price in rubber mill in correlation analysis. For regression analysis, the dominant factor that can affect the SMR profit price is the processing coot involve while the less dominant factor is maintenance cost. Lastly, it can be conclude that not only the rubber production factor can affect the SMR profit price, but other internal and external factor also can affect the profit price.